Safety and efficacy of avalglucosidase alfa versus alglucosidase alfa in patients with late-onset Pompe disease (COMET): a phase 3, randomised, multicentre trial. Issue 12 (December 2021) - Diaz-Manera, Jordi; Kishnani, Priya S; Kushlaf, Hani; Ladha, Shafeeq; Mozaffar, Tahseen; Straub, Volker; Toscano, Antonio; van der Ploeg, Ans T; Berger, Kenneth I; Clemens, Paula R; Chien, Yin-Hsiu; Day, John W; et al.
Summary: Background: Pompe disease is a rare, progressive neuromuscular disorder caused by deficiency of acid α-glucosidase (GAA) and accumulation of lysosomal glycogen. We assessed the safety and efficacy of avalglucosidase alfa, a recombinant human GAA enzyme replacement therapy specifically designed for enhanced mannose-6-phosphate-receptor targeting and enzyme uptake aimed at increased glycogen clearance, compared with the current approved standard of care, alglucosidase alfa, in patients with late-onset Pompe disease. Methods: We did a randomised, double-blind, phase 3 trial at 55 sites in 20 countries. We enrolled individuals (aged ≥3 years) with enzymatically confirmed late-onset Pompe disease who had never received treatment. We used a centralised treatment allocation system to randomly allocate participants to either avalglucosidase alfa or alglucosidase alfa. Participants and investigators were unaware of their treatment allocation. The primary outcome measure was change from baseline to week 49 in upright forced vital capacity percent (FVC%) predicted. We used a hierarchical fixed sequential testing strategy, whereby non-inferiority of avalglucosidase alfa compared with alglucosidase alfa was assessed first, with a non-inferiority margin of 1·1. If non-inferiority was seen, then superiority was tested with a 5% significance level. The key secondary objective was effect on functional endurance, measured by the 6-minute walk test (6MWT). Safety was assessed, including treatment-emergent adverse events and infusion-associated reactions. The modified intent-to-treat population was the primary analysis population for all efficacy analyses. The safety population was the analysis population for safety analyses. This trial is registered with ClinicalTrials.gov, NCT02782741 . We report results of the 49-week primary analysis period. Findings: Between Nov 2, 2016, and March 29, 2019, 100 participants were randomly allocated avalglucosidase alfa (n=51) or alglucosidase alfa (n=49). Treatment with avalglucosidase alfa resulted in a least-squares mean improvement in upright FVC% predicted of 2·89% (SE 0·88) compared with 0·46% (0·93) with alglucosidase alfa at week 49 (difference 2·43% [95% CI −0·13 to 4·99]). Non-inferiority was shown because the lower bound of the 95% CI for the difference far exceeded the predefined non-inferiority margin but did not exclude 0 (p=0·0074). Superiority was not reached (p=0·063), so formal testing was stopped, as per the testing hierarchy. Improvements were also seen in the 6MWT with avalglucosidase alfa compared with alglucosidase alfa, with greater increases in distance covered (difference 30·01 m [95% CI 1·33 to 58·69]) and percent predicted (4·71% [0·25 to 9·17]). Treatment-emergent adverse events potentially related to treatment were reported in 23 (45%) of 51 participants in the avalglucosidase alfa group and in 24 (49%) of 49 in the alglucosidase alfa group, and infusion-associated reactions were reported in 13 (26%) participants in the avalglucosidase alfa group and 16 (33%) in the alglucosidase alfa group. Of the five trial withdrawals, all in the alglucosidase alfa group, four were due to adverse events, including two infusion-associated reactions. Serious treatment-emergent adverse events were reported in eight (16%) participants who received avalglucosidase alfa and in 12 (25%) who received alglucosidase alfa. One participant treated with alglucosidase alfa died because of acute myocardial infarction determined to be unrelated to treatment. Antidrug antibody responses were similar in both groups. High and persistent titres (≥12 800) and neutralising antibodies were more common with alglucosidase alfa (in 16 [33%] participants) than with avalglucosidase alfa (ten [20%]). Interpretation: We consider that this study provides evidence of clinically meaningful improvement with avalglucosidase alfa therapy over alglucosidase alfa in respiratory function, ambulation, and functional endurance, with no new safety signals reported. An open-label extended-treatment period is ongoing to confirm the long-term safety and efficacy of avalglucosidase alfa, with the aim for this therapy to become the new standard treatment in late-onset Pompe disease. Funding: Sanofi Genzyme.